2009
DOI: 10.3748/wjg.15.927
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalized ulcerative colitis patients have an elevated risk of thromboembolic events

Abstract: AIM:To compare thromboembolism rates between hospitalized patients with a diagnosis of ulcerative colitis and other hospitalized patients at high risk for thromboembolism. To compare thromboembolism rates between patients with ulcerative colitis undergoing a colorectal operation and other patients undergoing colorectal operations. METHODS:Data from the National Hospital Discharge Survey was used to compare thromboembolism rates between (1) hospitalized patients with a discharge diagnosis of ulcerative colitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 35 publications
0
22
1
Order By: Relevance
“…Our VTE incidence of 5.3% (95% CI, 3.4–8.2%) is higher than the incidence of 2.03% (95% CI, 1.36–2.69%) quoted in an earlier study by Wang et al 9 which looked at VTE diagnosed on admission or at some point during admission. While the overall incidence of 6.1% perhaps represents the most appropriate risk for severe UC patients, the incidence of 4.5% (diagnosed during hospitalisation and within 1 month of discharge, but not on admission) better represents hospitalised UC patients’ risk for VTE.…”
Section: Discussioncontrasting
confidence: 83%
See 2 more Smart Citations
“…Our VTE incidence of 5.3% (95% CI, 3.4–8.2%) is higher than the incidence of 2.03% (95% CI, 1.36–2.69%) quoted in an earlier study by Wang et al 9 which looked at VTE diagnosed on admission or at some point during admission. While the overall incidence of 6.1% perhaps represents the most appropriate risk for severe UC patients, the incidence of 4.5% (diagnosed during hospitalisation and within 1 month of discharge, but not on admission) better represents hospitalised UC patients’ risk for VTE.…”
Section: Discussioncontrasting
confidence: 83%
“…On admission, the median C-reactive protein was 29 mg/L (IQR 7.7, 80.8) and haemoglobin was 12.1 g/dL (IQR 10.5, 13.4). The median length of stay was 6 days (IQR 3,9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible association between IBD and VTE was first reported in 1936 by Bargen and Barker, who described 18 patients with thromboembolic disease (predominantly venous) from among more than 1000 patients treated for IBD at the Mayo Clinic . Since that time, several recent publications have suggested that patients with IBD have an increased risk of VTE, although some heterogeneity can be seen in the literature . For example, while Nguyen et al .…”
Section: Introductionmentioning
confidence: 99%
“…10 Since that time, several recent publications have suggested that patients with IBD have an increased risk of VTE 11 , although some heterogeneity can be seen in the literature. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] For example, while Nguyen et al 17 reported that IBD patients may have a more than sevenfold increase in the risk of VTE, Saleh et al 21 identified a much lower risk.…”
Section: Introductionmentioning
confidence: 99%